Modelling the effect of access to information, political interest and policy satisfaction on youth online political participation in Malaysia - Aishat Adebisi Abdul Rauf,; Norsiah Abdul Hamid,; Mohd Sobhi Ishak, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The non-participation of youths in the politics of their nation is a global phenomenon. Yet not much research is being carried out in this area. Thus, this study conducted a cross sectional survey of 168 randomly selected Malaysian undergraduate students of Universiti Utara Malaysia (UUM) to find out if Access to Information on Facebook and Twitter (APIFT), Political Interest (PI) and Policy Satisfaction (PS) leads to Online Political Participation on Facebook and Twitter (OPPFT). Data was analyzed using Partial Least Squares - Structural Equation Modelling (PLSSEM). The results of this study revealed there is a significant positive relationship between APIFT, PI and OPPFT, however PS was not significantly related to OPPFT. This shows that while PS does not lead to OPPFT among youths in Malaysia, APIFT and PI promotes OPPFT among this group. Consequently, access to information and political interest could be used to engender Malaysian youth’s participation in politics. Aside empirically adding to the growing body of knowledge on political participation, this study has implication both in terms of theory and practice in the field of political communication.